Construction and Operations of First Salinity Gradient Solar Pond in Malaysia / Nuraida ‘Aadilia Baharin ...[et al.] - Baharin, Nuraida ‘Aadilia; Muhaimin Yazit, Idznie Faidhi; Bhathal Singh, Baljit Singh; Remeli, Muhammad Fairuz; Oberoi, Amandeep (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Solar pond is an integrated solar collector and storage. An experimental salinity gradient solar pond was constructed to analyse the thermal storage capability. The solar pond consist of 2.4 m², 1.4 m deep with sodium chloride (NaCl) as the salt solution. For the development of salinity gradient, a diffuser was used to develop the salinity gradient. The salinity gradient solar pond consists lower convective zone (LCZ) with a height of 0.5 m with 1200 kg/m3 density, non-convective zone (NCZ) with a height 0.8 m and upper convective zone (UCZ) with a height 10 cm. The temperature of (LCZ) as heat storage was recorded and analysed weekly. Maximum temperature of (LCZ) storage zone was recorded to be at 36.5 °C after four weeks and it showed and upward trend. The heat energy stored in (LCZ) can be used for power generation.